La teoría de la complejidad y su contribución al debate sobre las competencias académicas del ingeniero-docente universitario (2021)
In the fields of complexity theory, the subject of educational reforms is of great interest. When competency-based training is currently being promoted, Edgar Morin’s work is rich in multiple ideas that could contribute to enrich the debate, taking into account the challenges that the contemporary crisis imposes, both for scientific knowledge and for the study of human problems. This study aims to evaluate the contributions that from the theory of complexity could be incorporated into the competencies required of the engineer-teacher in order to overcome the challenges faced by humanity through the incorporation of knowledge that is still absent in current teaching.